Study of Diversity estimates of Yield and Yield Related Characters in Response to Nitrogen Fertilizers of Barley Genotypes (Bangladesh Journal of Genetics and Biotechnology, 2007)
Key words: Barley; Nitrogen fertilizer; Nitrogen utilizationBangladesh j. genet. biotechnol. 5 (1&2): 19-21, 2004 (June & December)